2010
DOI: 10.1093/pcp/pcq011
|View full text |Cite
|
Sign up to set email alerts
|

Two R2R3-MYB Genes, Homologs of Petunia AN2, Regulate Anthocyanin Biosyntheses in Flower Tepals, Tepal Spots and Leaves of Asiatic Hybrid Lily

Abstract: Anthocyanins are secondary metabolites that contribute to colors of flowers, fruits and leaves. Asiatic hybrid lily (Lilium spp.) accumulates cyanidin anthocyanins in flower tepals, tepal spots and leaves of juvenile shoots. To clarify their mechanisms of regulation of anthocyanin pigmentation, two full-length cDNAs of R2R3-MYB (LhMYB6 and LhMYB12) were isolated from the anthocyanin-accumulating tepals of cultivar 'Montreux'. Analysis of the deduced amino acid sequences indicated they have homology with petuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
173
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(185 citation statements)
references
References 43 publications
8
173
0
4
Order By: Relevance
“…Several researchers have shown that AN2 or UPA20 proteins from different species are highly conserved (Quattrocchio et al, 1999;Griesbach, 2002;Kay et al, 2007;Zhou and Chai, 2008;van der Hoorn and Kamoun, 2008;Yamagishi et al, 2010). Therefore, tomato can be used as a model organism to study pepper AN2 and UPA20 or pepper can be used as a model organism to study tomato, potato, or tobacco AN2 and UPA20 genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have shown that AN2 or UPA20 proteins from different species are highly conserved (Quattrocchio et al, 1999;Griesbach, 2002;Kay et al, 2007;Zhou and Chai, 2008;van der Hoorn and Kamoun, 2008;Yamagishi et al, 2010). Therefore, tomato can be used as a model organism to study pepper AN2 and UPA20 or pepper can be used as a model organism to study tomato, potato, or tobacco AN2 and UPA20 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Many genes encoding AN2 and UPA20 from several plant species have been isolated and characterized at the genetic, chemical, and enzymological levels (Quattrocchio et al, 1999;Griesbach, 2002;Kay et al, 2007;Zhou and Chai, 2008;van der Hoorn and Kamoun, 2008;Yamagishi et al, 2010). However, the AN2 and UPA20 genes from pepper have not been previously cloned.…”
Section: Discussionmentioning
confidence: 99%
“…A few novel R2R3MYB genes have recently been characterized in petunia: DEEP PURPLE (DPL) regulating vein-associated anthocyanin pigmentation in flower tubes and PURPLE HAZE (PHZ) determining light-induced anthocyanin accumulation on exposed petal surfaces (bud-blush) (Albert et al 2011). In Asiatic hybrid lilies, LhMYB6 and LhMYB12 together with LhbHLH2 regulate anthocyanin pigmentation in specific organs (Yamagishi et al 2010). LhMYB6 was first reported to correlate with anthocyanin spots in tepals (Yamagishi et al 2010), but LhMYB12-Lat, an another allele of LhMYB12, has also been shown to be involved in splatter-type spot formation in flower tepals (Yamagishi et al 2014).…”
Section: Transcription Factors Responsible For Anthocyanin Biosynthesmentioning
confidence: 99%
“…In Asiatic hybrid lilies, LhMYB6 and LhMYB12 together with LhbHLH2 regulate anthocyanin pigmentation in specific organs (Yamagishi et al 2010). LhMYB6 was first reported to correlate with anthocyanin spots in tepals (Yamagishi et al 2010), but LhMYB12-Lat, an another allele of LhMYB12, has also been shown to be involved in splatter-type spot formation in flower tepals (Yamagishi et al 2014). Japanese gentians might also have other transcription factor genes regulating color intensity and patterning, a point that should be considered as a future research theme.…”
Section: Transcription Factors Responsible For Anthocyanin Biosynthesmentioning
confidence: 99%
“…In lily cultivars, variation in flower color is among the most important targets of cultivar breeding programs and is produced by variation in the accumulation of anthocyanin and carotenoid pigments (Yamagishi 2013). Several genes involved in anthocyanin and carotenoid biosyntheses have been studied in lilies (Jeknić et al 2012;Lai et al 2012;Nakatsuka et al 2003Nakatsuka et al , 2009Yamagishi et al 2010aYamagishi et al , 2010b. Recently, the transcriptomes of several lily organs have been sequenced using next-generation sequencing (NGS), and a variety of potentially important novel genes have been identified Villacorta-Martin et al 2015;Wang et al 2014), although their specific functions remain to be determined.…”
mentioning
confidence: 99%